Low-radiation coated glass and preparation method thereof
By using high-melting point metal element and amorphous nitride barrier layer in low-radiation coated glass, combined with Cu film, the problems of high-temperature oxidation and agglomeration are solved, the insulation performance and transmittance of the glass are improved, and the reflectivity and Emissivity.
Patent Information
- Application Number
- CN202411275535.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing low-radiation coating glass is easily oxidized and agglomerated after high-temperature heat treatment, resulting in a decrease in transmittance and poor color uniformity. The traditional metal barrier layer material is easy to react with the Cu film, affecting performance.
Use high-melting point metal element such as W, Mn, Ta, Ge or Pd as the barrier layer, and form a dense amorphous nitride, silicon nitride and other barrier layers by blending elements such as N, Si, C, and B, and combine Ag or Cu. The film can avoid Cu reacting with the barrier layer, and use materials such as high-hardness silicon nitride as the top dielectric layer to enhance the scratch resistance and heat treatment stability of the film layer.
The high temperature stability and visible light transmittance of low-radiation coated glass are achieved, the reflectivity and radiation rate are reduced, and the thermal insulation performance and scratch resistance of coated glass are improved.
Smart Images

Figure CN119118534A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coated glass, and in particular to a low-radiative coated glass and a preparation method thereof. Background Art
[0002] Low-emissivity coated glass, also known as energy-saving glass, is made by depositing multiple layers of thin film on float glass through physical sputtering. The metal Ag film or Cu film has the ability to reflect infrared rays, making the coated glass heat-insulating and heat-preserving. It is widely used in the fields of building glass curtain walls, transportation vehicle windows, etc.
[0003] Among them, the metal Cu film is more active than the Ag film because of its chemical properties. At present, the low-emissivity film system containing Cu film on the market generally cannot be heat-treated at 700℃. The main reason is that after the heat treatment, serious mutual diffusion oxidation and agglomeration occur between the film layers, resulting in increased scattering of light on the film surface, forming a certain haze, resulting in a decrease in transmittance. In order to prevent the film layer from being oxidized when placed in the air for a long time or during high-temperature heat treatment, a barrier protective layer is usually covered on it.
[0004] In the existing process, the barrier protective layer usually uses metals such as NiCr, Al, and Ti. Although the above metal structures are dense, heat-resistant, and have strong oxygen absorption capacity, metal Cu is easy to react with NiCr, Al, Ti, etc. to form alloy phases during heat treatment, which affects the performance and color uniformity of low-emissivity glass. In addition, the extinction coefficient of the metal barrier protective layer is generally large, and the absorption effect on light is strong. When it is applied to the barrier layer, a slight increase in thickness will cause the light transmission performance of the coated glass to drop rapidly. Coated glass has certain requirements for optical color, and neutral transmitted color is more favored by the market. When the thickness of the metal barrier layer increases, problems such as darker film color and poor color uniformity after heat treatment will occur.
[0005] For example, CN109399958A discloses a low-reflectivity, low-emissivity coated glass, which is formed by setting a NiCr layer as a protective layer. The thickness of the first protective layer is 1.5-5nm, and the thickness of the second protective layer is 2.3-10nm. Although it can serve as a protective functional layer, the color uniformity is poor after heat treatment, and the color of the film layer is darker.
[0006] Therefore, how to protect the metal functional layer in the low-emissivity coated glass from being oxidized and agglomerated after high-temperature heat treatment to ensure a low heat transfer coefficient and high infrared reflection performance is a technical problem that needs to be solved in this field. Summary of the invention
[0007] In view of the above problems, the purpose of the present invention is to provide a low-radiation coated glass and a preparation method thereof. Compared with the prior art, the low-radiation coated glass provided by the present invention avoids using the traditional NiCr film as a metal barrier layer, ensuring that the low-radiation glass with a Cu film can be heat-treated. In addition, the problem of low visible light transmittance caused by the thick NiCr film layer is solved, and the glass has low radiation performance and low reflectivity, which can improve the scratch resistance of the coated glass and the stability during heat treatment.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a low-emissivity coated glass, the low-emissivity coated glass comprising a glass substrate and a coating layer disposed on one side of the glass substrate;
[0010] The coating layer includes a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, which are sequentially plated from one side of the glass substrate to the outside;
[0011] Wherein, the first barrier layer, the second barrier layer and the third barrier layer are each independently a metal barrier layer and / or a nitrogen-containing barrier layer;
[0012] The metal single substance barrier layer includes any one of W, Mn, Ta, Ge or Pd;
[0013] The nitrogen-containing barrier layer comprises any one or a combination of at least two of nitride, silicon nitride, silicon carbon nitride or silicon boron nitride of a metal material;
[0014] The metal material includes any one of Ta, Ti, Zn, Al or Hf, or a combination of at least two of them.
[0015] In the low-emissivity coated glass provided by the present invention, the anti-oxidation effect of the functional layer and the improvement of the visible light transmittance are achieved mainly by improving the barrier layer and the top dielectric layer, especially the improvement of the barrier layer. Among them, the improvement of the barrier layer mainly includes two aspects: on the one hand, by using W, Mn, Ta, Ge, Pd and other metal single substances with good density and stability and high melting point (melting point above 1200°C) as barrier layer materials, the dense structure can be used to protect the Ag or Cu film, and at the same time, the Cu film is not easy to react with it at high temperature, and the diffusion coefficient is low, which can maintain a stable interface structure between film layers; on the other hand, by using nitrides, silicon nitrides, silicon carbon nitrides of Ta, Ti, Zn, Al or Hf and their alloys Nitrides, silicon boron nitrides, etc. are used as barrier layer materials. By adding N, Si, C, B and other elements to the above metals and their alloys, the crystal structure can be destroyed to form dense amorphous nitrides, silicon nitrides, silicon carbon nitrides, and silicon boron nitrides, which have good high temperature resistance and can further enhance the protection of the functional layer. Some nitride films such as TaN have good light transmittance. At the same time, the diffusion coefficient of Cu in TaN is low, and the interface between Cu and TaN is stable and not easy to react, which can improve the oxidation resistance and heat resistance of the Cu film.
[0016] Preferably, the primer layer comprises a sulfide of the first media precursor.
[0017] Preferably, the first medium precursor includes any one of Zn, ZnCd, ZnMn, ZnAl or ZnTi, or a combination of at least two thereof.
[0018] In the present invention, it is further preferred to control the base layer to use sulfides such as Zn, ZnCd, ZnMn, ZnAl or ZnTi, which can use its dense amorphous structure to block the alkali ions in the glass from diffusing into the film layer at high temperature to avoid damage to it, and the high refractive index film layer structure can eliminate the reflection of light inside the film layer and increase the light transmittance of the product.
[0019] Preferably, the first seed layer, the second seed layer and the third seed layer each independently contain any one of indium zinc oxide, fluorine tin oxide, gallium zinc oxide, indium gallium zinc oxide, manganese tin oxide, zinc aluminum oxide or tin antimony oxide, or a combination of at least two thereof.
[0020] In the present invention, the above-mentioned doped oxide film layer is preferably used, which has good conductivity and can reduce the overall resistivity of the radiation glass. The doped and modified oxide film layer has a higher carrier concentration inside, which can play an auxiliary role in the infrared reflection of the low-emissivity glass. In addition, the above-mentioned doped oxide film layer has good stability and is not easy to fail during subsequent heat treatment.
[0021] Preferably, the first functional layer, the second functional layer and the third functional layer each independently include any one of Ag film, Cu film, AgCuTi alloy film, AgCuTa alloy film, AgCuMo alloy film or AgCuNb alloy film, or a combination of at least two thereof.
[0022] In the present invention, it is preferred to use the above-mentioned metal film layer as the functional layer, such as Ag and Cu films, which have lower resistivity and infrared light reflection performance. Since the resistivity and emissivity are proportional, lower resistivity can obtain lower radiation performance, and Cu can improve the film layer's transmittance color, making the color more neutral, and making metal Ag or Cu into a multi-element alloy film can further enhance the oxidation resistance and heat resistance of the low-emissivity glass.
[0023] Preferably, the top dielectric layer comprises any one of silicon nitride, silicon carbon nitride, silicon boron nitride, silicon carbon nitride oxide or silicon boron nitride oxide of the second dielectric precursor, or a combination of at least two thereof.
[0024] Preferably, the second medium precursor includes any one of Hf, Zr, Mo, Ti or Al, or a combination of at least two thereof.
[0025] In the present invention, the top dielectric layer is further preferably controlled to use silicon nitride, silicon carbon nitride, silicon boron nitride, silicon carbon nitride oxide or silicon boron nitride oxide of Hf, Zr, Mo, Ti, Al or their alloys, which can utilize their higher hardness to enhance the scratch resistance of the film surface, and silicon nitride, silicon carbon nitride, silicon boron nitride, silicon carbon nitride oxide or silicon boron nitride oxide have good high temperature resistance, and gradual oxidation occurs from the surface to the inside during heat treatment, thereby slowing down the rate of oxygen diffusion into the film.
[0026] Preferably, the thickness of the coating layer is 10-150nm, for example, it can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm or 150nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the thickness of the first seed layer is 20-48nm, for example, it can be 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm or 48nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the thickness of the first functional layer is 4-20 nm, for example, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the thickness of the first barrier layer is 0.5-30nm, for example, it can be 0.5nm, 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm or 30nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the thickness of the second functional layer is 4-20 nm, for example, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the thickness of the second barrier layer is 0.5-30 nm, for example, it can be 0.5 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm or 30 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the thickness of the second seed layer is 20-95 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 95 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the thickness of the third functional layer is 4-20 nm, for example, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the thickness of the third barrier layer is 0.5-30nm, for example, it can be 0.5, 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm or 30nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In the present invention, it is preferred to control the thickness of the first barrier layer, the second barrier layer and the third barrier layer within a specific range, so as to avoid the barrier layer being too thick, thereby avoiding excessive reduction in visible light transmittance.
[0036] Preferably, the thickness of the top dielectric layer is 30-150 nm, for example, it can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm or 150 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In a second aspect, the present invention provides a method for preparing the low-emissivity coated glass as described in the first aspect of the present invention, the preparation method comprising: performing magnetron sputtering on the surface of a glass substrate using a target material in a vacuum environment, and sputtering in sequence to form a base layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer to obtain the low-emissivity coated glass.
[0038] In the present invention, by adopting magnetron sputtering to sequentially plate a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, a low-emissivity coated glass with high visible light transmittance, low radiation performance, low reflectivity, good scratch resistance and thermal stability can be obtained.
[0039] Specifically, the preparation method comprises:
[0040] S1: Clean and dry the glass substrate;
[0041] S2: Place the glass substrate into the vacuum chamber to complete the transition from atmosphere to vacuum;
[0042] S3: Perform magnetron sputtering to complete the coating layers in sequence.
[0043] In the present invention, the coating of the base layer, seed layer, and functional layer can all be obtained by conventional magnetron sputtering processes for coating the above-mentioned film layers in the art. Among them, the coating of the base layer can be obtained, for example, by sputtering a target material corresponding to the first medium in pure argon; the coating of the seed layer can be obtained, for example, by sputtering a corresponding oxide target material in a mixed atmosphere of argon and trace oxygen; the coating of the functional layer can be obtained, for example, by sputtering a target material corresponding to a metal or alloy in pure argon gas.
[0044] Preferably, when preparing the metal single substance barrier layer in the magnetron sputtering, the target material used includes any one of a W target, a Mn target, a Ta target, a Ge target or a Pd target.
[0045] Preferably, when the metal single substance barrier layer is prepared by magnetron sputtering, the sputtering atmosphere used includes argon.
[0046] Preferably, when the metal element barrier layer is prepared by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa, for example, it can be 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa or 1Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In the present invention, the metal element barrier layer is obtained by sputtering the above-mentioned target material in a pure argon atmosphere, wherein parameters such as the sputtering power can adopt conventional values of the target material in the field, generally between 0.2-1kW, for example, it can be 0.2kW, 0.3kW, 0.4kW, 0.5kW, 0.6kW, 0.7kW, 0.8kW, 0.9kW or 1kW, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, when the nitrogen-containing barrier layer is prepared by magnetron sputtering, the target material used includes any one of a Ta target, a SiTi target, a SiZn target, a SiHf target, a SiTiC target or a SiAlB target, or a combination of at least two of them.
[0049] Preferably, when the nitrogen-containing barrier layer is prepared by magnetron sputtering, the sputtering atmosphere used includes argon and nitrogen.
[0050] Preferably, when preparing the nitrogen-containing barrier layer by magnetron sputtering, the gas flow ratio of argon and nitrogen is (2-6):(3-7), for example, it can be 2:3, 2:5, 2:7, 4:3, 4:5, 4:7, 6:3, 6:5 or 6:7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, when the nitrogen-containing barrier layer is prepared by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa, for example, it can be 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa or 1Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In the present invention, the nitrogen-containing barrier layer is obtained by sputtering the above-mentioned target material in a mixed atmosphere of nitrogen and argon, wherein parameters such as sputtering power can adopt conventional values of the target material in the field, for example, generally 1-3kW, for example, 1kW, 1.5kW, 2kW, 2.5kW or 3kW, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] Preferably, when preparing the top dielectric layer in the magnetron sputtering, the target material used includes any one of SiHf target, SiZr target, SiMo target, SiAl target, SiTiB target or SiAlC target, or a combination of at least two of them.
[0054] Preferably, when the top dielectric layer is prepared by magnetron sputtering, the sputtering atmosphere used includes a mixed atmosphere of argon and nitrogen or a mixed atmosphere of argon, nitrogen and oxygen.
[0055] Preferably, when preparing the top dielectric layer in the magnetron sputtering, the gas flow ratio of argon and nitrogen in the mixed atmosphere of argon and nitrogen is (2-6):(3-7), for example, it can be 2:3, 2:5, 2:7, 4:3, 4:5, 4:7, 6:3, 6:5 or 6:7, but is not limited to the listed values, and other values not listed in the numerical range are also applicable; or the gas flow ratio of argon, nitrogen and oxygen in the mixed atmosphere of argon, nitrogen and oxygen is (2-6):(3-7):(1-4), for example, it can be 2:3:1, 2:5:2, 2:7:3, 4:3:4, 4:5:1, 4:7:2, 6:3:3, 6:5:4 or 6:7:1, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0056] Preferably, when preparing the top dielectric layer by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa, for example, it can be 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa or 1Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In the present invention, the top dielectric layer can be obtained by sputtering a target material corresponding to the second dielectric in an atmosphere of argon and nitrogen, and parameters such as the sputtering power can adopt conventional values in the art, generally 1-3kW, for example, 1kW, 1.5kW, 2kW, 2.5kW or 3kW, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The low-emissivity coated glass provided by the present invention can ensure a lower emissivity and a lower heat transfer coefficient of the coated glass by sequentially arranging a base layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer from the inside to the outside, and can have good thermal insulation performance.
[0060] (2) The low-emissivity coated glass provided by the present invention has a first barrier layer, a second barrier layer and a third barrier layer. On the one hand, high-melting-point metals such as W, Mn, Ta, Ge or Pd are used as barrier layer materials, and their dense structure can be used to protect Ag or Cu films and prevent the diffusion and oxidation of Cu atoms at high temperatures. On the other hand, nitrides, silicon nitrides, silicon carbon nitrides or silicon boron nitrides of Ta, Ti, Zn, Al or Hf and their alloys are used, and elements such as N, Si, C, B are doped to destroy the crystal structure to form a dense amorphous material, which has good high-temperature resistance, can further enhance the protection of the functional layer, ensure a high visible light transmittance, and at the same time have a low reflectivity.
[0061] (3) The low-emissivity coated glass provided by the present invention improves the top dielectric layer and adopts silicon nitride, silicon carbon nitride, silicon boron nitride, silicon carbon nitride oxide or silicon boron nitride oxide of Hf, Zr, Mo, Ti or Al or their alloys, etc., which can utilize their higher hardness to enhance the scratch resistance of the film surface and the stability during heat treatment, and further prevent the oxidation and diffusion of the functional layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram of the structure of the low-emissivity coated glass according to Example 1 of the present invention;
[0063] Among them, 101 is a glass substrate; 102 is a base layer; 103 is a first seed layer; 104 is a first functional layer; 105 is a first barrier layer; 106 is a second functional layer; 107 is a second barrier layer; 108 is a second seed layer; 109 is a third functional layer; 110 is a third barrier layer; 111 is a top dielectric layer. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] Example 1
[0066] This embodiment provides a low-emissivity coated glass, such as Figure 1 As shown, the low-emissivity coated glass includes a glass substrate 101 and a coating layer disposed on one side of the glass substrate 101;
[0067] The coating layer includes a base layer 102, a first seed layer 103, a first functional layer 104, a first barrier layer 105, a second functional layer 106, a second barrier layer 107, a second seed layer 108, a third functional layer 109, a third barrier layer 110 and a top dielectric layer 111, which are sequentially plated from one side of the glass substrate 101 to the outside;
[0068] Specifically, the film composition and thickness are shown in Table 1:
[0069] Table 1
[0070] Elemental composition Thickness / mm Base ZnS 12.5 First seed layer AZO 37.2 The first functional layer Ag 7.2 First barrier layer T N 2.2 Second functional layer Cu 6.4 Second barrier layer T N 15 Second seed layer AZO 82.9 The third functional layer Ag 11.5 The third barrier layer T N 4.9 Top dielectric layer SiAlCN 39.5
[0071] This embodiment also provides a method for preparing the low-E coated glass, the method comprising: performing magnetron sputtering on the surface of a glass substrate 101 using a target material in a vacuum environment, and sequentially sputtering to form a base layer 102, a first seed layer 103, a first functional layer 104, a first barrier layer 105, a second functional layer 106, a second barrier layer 107, a second seed layer 108, a third functional layer 109, a third barrier layer 110 and a top dielectric layer 111, to obtain the low-E coated glass;
[0072] Specifically include:
[0073] S1: Clean and dry the glass substrate;
[0074] S2: Place the glass substrate into the vacuum chamber to complete the transition from atmosphere to vacuum;
[0075] S3: magnetron sputtering is performed with ZnS as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW to obtain a base layer 102;
[0076] S4: magnetron sputtering is performed with AZO as the target material, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW, to obtain the first seed layer 103;
[0077] S5: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW, to obtain the first functional layer 104;
[0078] S6: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon and nitrogen, the gas flow ratio is 2:5, the sputtering pressure is 0.45 Pa, and the sputtering power is 0.2 kW, to obtain the first barrier layer 105;
[0079] S7: magnetron sputtering is performed with Cu as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the second functional layer 106;
[0080] S8: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon and nitrogen, the gas flow ratio is 2:5, the sputtering pressure is 0.45 Pa, and the sputtering power is 1.2 kW, to obtain the second barrier layer 107;
[0081] S9: magnetron sputtering is performed with AZO as the target material, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW, to obtain a second seed layer 108;
[0082] S10: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW, to obtain the third functional layer 109;
[0083] S11: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon gas and nitrogen gas, the gas flow ratio is 2:5, the sputtering pressure is 0.45 Pa, and the sputtering power is 1.2 kW, to obtain a third barrier layer 110;
[0084] S12: Magnetron sputtering is performed with SiAlC as a target material, the atomic percentage of Si, Al and C in the SiAlC target material is 80:10:10, the atmosphere is argon and nitrogen, the gas flow ratio is 6:5, the sputtering pressure is 0.25 Pa, the sputtering power is 3 kW, and a top dielectric layer 111 is obtained.
[0085] Example 2
[0086] This embodiment provides a low-radiation coated glass and a preparation method thereof, wherein the low-radiation coated glass comprises a glass substrate and a coating layer disposed on one side of the glass substrate;
[0087] The coating layer includes a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, which are sequentially plated from one side of the glass substrate to the outside;
[0088] Specifically, the film composition and thickness are shown in Table 2:
[0089] Table 2
[0090]
[0091]
[0092] This embodiment also provides a method for preparing the low-E coated glass, the method comprising: performing magnetron sputtering on the surface of a glass substrate using a target material in a vacuum environment, and sequentially sputtering to form a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, to obtain the low-E coated glass;
[0093] Specifically include:
[0094] S1: Clean and dry the glass substrate;
[0095] S2: Place the glass substrate into the vacuum chamber to complete the transition from atmosphere to vacuum;
[0096] S3: magnetron sputtering was performed with ZnCdS as the target material, the atomic percentage of Zn, Cd and S in the ZnCdS target material was 40:10:50, the atmosphere was argon, the sputtering pressure was 0.2 Pa, the sputtering power was 1 kW, and a base layer was obtained;
[0097] S4: magnetron sputtering is performed with IZO as the target, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW to obtain the first seed layer;
[0098] S5: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the first functional layer;
[0099] S6: magnetron sputtering is performed with SiTiC as the target material, the atomic percentage of Si, Ti and C in the SiTiC target material is 80:10:10, the atmosphere is argon and nitrogen, the gas flow ratio is 6:5, and the sputtering power is 1 kW, to obtain the first barrier layer;
[0100] S7: magnetron sputtering is performed with Cu as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the second functional layer;
[0101] S8: magnetron sputtering is performed with SiTiC as the target material, the atomic percentage of Si, Ti and C in the SiTiC target material is 80:10:10, the atmosphere is argon and nitrogen, the sputtering pressure is 0.25 Pa, the gas flow ratio is 6:5, and the sputtering power is 1 kW, to obtain a second barrier layer;
[0102] S9: magnetron sputtering is performed with IZO as the target, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW to obtain the second seed layer;
[0103] S10: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the third functional layer;
[0104] S11: magnetron sputtering is performed with SiTiC as a target material, the atomic percentage of Si, Ti and C in the SiTiC target material is 80:10:10, the atmosphere is argon and nitrogen, the sputtering pressure is 0.25 Pa, the gas flow ratio is 6:5, and the sputtering power is 1 kW, to obtain a third barrier layer;
[0105] S12: Magnetron sputtering is performed with SiHf as the target material, the atomic percentage of Si and Hf in the SiHf target material is 80:20, the atmosphere is argon and nitrogen, the sputtering pressure is 0.25 Pa, the gas flow ratio is 6:5, and the sputtering power is 3 kW to obtain a top dielectric layer.
[0106] Example 3
[0107] This embodiment provides a low-radiation coated glass and a preparation method thereof, wherein the low-radiation coated glass comprises a glass substrate and a coating layer disposed on one side of the glass substrate;
[0108] The coating layer includes a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, which are sequentially plated from one side of the glass substrate to the outside;
[0109] Specifically, the film composition and thickness are shown in Table 3:
[0110] Table 3
[0111]
[0112]
[0113] This embodiment also provides a method for preparing the low-E coated glass, the method comprising: performing magnetron sputtering on the surface of a glass substrate using a target material in a vacuum environment, and sequentially sputtering to form a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, to obtain the low-E coated glass;
[0114] Specifically include:
[0115] S1: Clean and dry the glass substrate;
[0116] S2: Place the glass substrate into the vacuum chamber to complete the transition from atmosphere to vacuum;
[0117] S3: magnetron sputtering was performed using ZnMnS as a target material, the atomic percentage of Zn, Mn and S in the ZnMnS target material was 40:10:50, the atmosphere was argon, the sputtering pressure was 0.2 Pa, and the sputtering power was 1 kW to obtain a base layer;
[0118] S4: magnetron sputtering is performed with GZO as the target material, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW to obtain the first seed layer;
[0119] S5: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the first functional layer;
[0120] S6: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the first barrier layer;
[0121] S7: magnetron sputtering is performed with Cu as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the second functional layer;
[0122] S8: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the second barrier layer;
[0123] S9: magnetron sputtering is performed with GZO as the target material, the atmosphere is argon and oxygen, the gas flow ratio is 16:1, the sputtering pressure is 0.2 Pa, and the sputtering power is 1 kW to obtain the second seed layer;
[0124] S10: magnetron sputtering is performed with Ag as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain the third functional layer;
[0125] S11: magnetron sputtering is performed with Ta as the target material, the atmosphere is argon, the sputtering pressure is 0.2 Pa, and the sputtering power is 0.2 kW to obtain a third barrier layer;
[0126] S12: Magnetron sputtering is performed with SiTiB as the target material, the atomic percentage of Si, Ti and B in the SiTiB target material is 80:10:10, the atmosphere is argon and nitrogen, the sputtering pressure is 0.25 Pa, the gas flow ratio is 6:5, the sputtering power is 3 kW, and a top dielectric layer is obtained.
[0127] Example 4
[0128] This embodiment provides a low-emissivity coated glass, which is different from Embodiment 1 only in that the first barrier layer, the second barrier layer and the third barrier layer are all metal W films.
[0129] Example 5
[0130] This comparative example provides a low-emissivity coated glass, which is different from Example 1 only in that the base layer and the top dielectric layer are both silicon nitride films.
[0131] Comparative Example 1
[0132] This comparative example provides a low-emissivity coated glass, which is different from that of Example 1 only in that the first barrier layer, the second barrier layer and the third barrier layer are all NiCr alloy films.
[0133] The low-emissivity coated glass prepared in Examples 1-5 and Comparative Example 1 was heat-treated at 700° C. for 450 seconds. The reflectivity, heat transfer coefficient, transmittance and emissivity after the heat treatment are shown in Table 4.
[0134] Table 4
[0135] Reflectivity / % <![CDATA[Heat transfer coefficient / (W·m -1 ·K -1 )]]> Transmittance / % Emissivity Example 1 11.2 1.33 63.4 0.05 Example 2 10.5 1.42 65.1 0.06 Example 3 13.1 1.45 58.6 0.06 Example 4 13.4 1.54 57.3 0.07 Example 5 16.4 2.25 55.1 0.82 Comparative Example 1 17.6 2.13 53.6 0.81
[0136] From the data in Table 4, we can see the following points:
[0137] (1) From the data of Examples 1-4, it can be seen that the low-emissivity coated glass provided by the present invention can reduce the reflectivity to below 13.4%, the emissivity to below 0.07, and the heat transfer coefficient to 1.54 W·m -1 ·K -1 Below, the transmittance reaches more than 57.3%, which can ensure a high visible light transmittance, while the reflectivity and emissivity are low.
[0138] (2) The only difference between Example 1 and Example 5 is that in Example 5, both the base layer and the top dielectric layer are made of silicon nitride. The reflectivity and emissivity in Example 1 are significantly lower than those in Example 5, and the heat transfer coefficient is significantly lower than that in Example 5. Meanwhile, the transmittance is higher than that in Example 5. It can be seen that the present invention can further prevent the oxidation and diffusion of the functional layer by preferentially controlling the composition of the base layer and the top dielectric layer, so that the coated glass has good thermal insulation and high visible light transmittance.
[0139] (3) The only difference between Example 1 and Comparative Example 1 is that the first barrier layer, the second barrier layer and the third barrier layer in Comparative Example 1 all use the NiCr alloy commonly used in the prior art. The results show that by controlling the material of the barrier layer in the present invention, the functional layer can be effectively protected to avoid its diffusion and oxidation at high temperature, so that the coated glass can achieve good thermal insulation and high visible light transmittance.
[0140] In summary, the low-emissivity coated glass provided by the present invention can provide good protection for the functional layer, and also has low-emissivity and low reflectivity, and has high transmittance, and has broad application prospects.
[0141] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A low-emissivity coated glass, characterized in that: The low-emissivity coated glass comprises a glass substrate and a coating layer arranged on one side of the glass substrate; The coating layer includes a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, which are sequentially plated from one side of the glass substrate to the outside; Wherein, the first barrier layer, the second barrier layer and the third barrier layer are each independently a metal barrier layer and / or a nitrogen-containing barrier layer; The metal single substance barrier layer includes any one of W, Mn, Ta, Ge or Pd; The nitrogen-containing barrier layer comprises any one or a combination of at least two of nitride, silicon nitride, silicon carbon nitride or silicon boron nitride of a metal material; The metal material includes any one of Ta, Ti, Zn, Al or Hf, or a combination of at least two of them.
2. The low-emissivity coated glass according to claim 1, characterized in that: The primer layer includes a sulfide of a first medium precursor; Preferably, the first medium precursor includes any one of Zn, ZnCd, ZnMn, ZnAl or ZnTi, or a combination of at least two thereof.
3. The low-emissivity coated glass according to claim 1 or 2, characterized in that: The first seed layer, the second seed layer and the third seed layer each independently contain any one of indium zinc oxide, fluorine tin oxide, gallium zinc oxide, indium gallium zinc oxide, manganese tin oxide, zinc aluminum oxide or tin antimony oxide, or a combination of at least two thereof.
4. The low-emissivity coated glass according to any one of claims 1 to 3, characterized in that: The first functional layer, the second functional layer and the third functional layer each independently include any one of Ag film, Cu film, AgCuTi alloy film, AgCuTa alloy film, AgCuMo alloy film or AgCuNb alloy film or a combination of at least two thereof.
5. The low-emissivity coated glass according to any one of claims 1 to 4, characterized in that: The top dielectric layer comprises any one or a combination of at least two of silicon nitride, silicon carbon nitride, silicon boron nitride, silicon carbon nitride oxide or silicon boron nitride oxide of the second dielectric precursor; Preferably, the second medium precursor includes any one of Hf, Zr, Mo, Ti or Al, or a combination of at least two thereof.
6. The low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the bottom layer is 10-150nm; Preferably, the thickness of the first seed layer is 20-48 nm; Preferably, the thickness of the first functional layer is 4-20 nm; Preferably, the thickness of the first barrier layer is 0.5-30 nm; Preferably, the thickness of the second functional layer is 4-20 nm; Preferably, the thickness of the second barrier layer is 0.5-30 nm; Preferably, the thickness of the second seed layer is 20-95 nm; Preferably, the thickness of the third functional layer is 4-20 nm; Preferably, the thickness of the third barrier layer is 0.5-30 nm; Preferably, the thickness of the top dielectric layer is 30-150 nm.
7. A method for preparing the low-emissivity coated glass according to any one of claims 1 to 6, characterized in that: The preparation method comprises: performing magnetron sputtering on the surface of a glass substrate using a target material in a vacuum environment, and sequentially sputtering to form a primer layer, a first seed layer, a first functional layer, a first barrier layer, a second functional layer, a second barrier layer, a second seed layer, a third functional layer, a third barrier layer and a top dielectric layer, to obtain the low-emissivity coated glass.
8. The preparation method according to claim 7, characterized in that: When the metal single substance barrier layer is prepared by magnetron sputtering, the target material used includes any one of a W target, a Mn target, a Ta target, a Ge target or a Pd target; Preferably, when the metal element barrier layer is prepared by magnetron sputtering, the sputtering atmosphere used includes argon; Preferably, when the metal single substance barrier layer is prepared by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa.
9. The preparation method according to claim 7 or 8, characterized in that: When the nitrogen-containing barrier layer is prepared by magnetron sputtering, the target material used includes any one of Ta target, SiTi target, SiZn target, SiHf target, SiTiC target or SiAlB target, or a combination of at least two of them; Preferably, when the nitrogen-containing barrier layer is prepared by magnetron sputtering, the sputtering atmosphere used includes argon and nitrogen; Preferably, when preparing the nitrogen-containing barrier layer in the magnetron sputtering, the gas flow ratio of argon gas to nitrogen gas is (2-6):(3-7); Preferably, when the nitrogen-containing barrier layer is prepared by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa.
10. The preparation method according to any one of claims 7 to 9, characterized in that: When the top dielectric layer is prepared by magnetron sputtering, the target material used includes any one of SiHf target, SiZr target, SiMo target, SiAl target, SiTiB target or SiAlC target, or a combination of at least two thereof; Preferably, when preparing the top dielectric layer in the magnetron sputtering, the sputtering atmosphere used includes a mixed atmosphere of argon and nitrogen or a mixed atmosphere of argon, nitrogen and oxygen; Preferably, when preparing the top dielectric layer in the magnetron sputtering, the gas flow ratio of argon and nitrogen in the mixed atmosphere of argon and nitrogen is (2-6):(3-7) or the gas flow ratio of argon, nitrogen and oxygen in the mixed atmosphere of argon, nitrogen and oxygen is (2-6):(3-7):(1-4); Preferably, when the top dielectric layer is prepared by magnetron sputtering, the sputtering gas pressure is 0.2-1Pa.
Citation Information
Patent Citations
Low-reflectivity low-emissivity coating glass and preparing method thereof
CN109399958A
Cited By
Infrared-barrier low-sheet-resistance AZO coated glass and preparation method thereof
CN120328876A
Functional layer of Low-E coated glass, Low-E coated glass and preparation method of Low-E coated glass
CN122167036A
A functional layer of Low-E coated glass, Low-E coated glass and its preparation method
CN122167036B
